Patterns of Neck Node Metastasis in Carcinoma of Oral Cavity - Ahmed, Shamsuddin; Delwar, AHM; Mazumder, Jahangir Alam; Rashid, M Sazibur; Khan, M Arif Murshed; Mahamud, Mashuque; Rahman, Md Mostafizur (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To find out the patterns of cervical lymph node metastasis in oral cavity carcinoma. Methods: This is across sectional study which was carried out in the department of Otolaryngology & Head Neck Surgery Dhaka Medical College Hospital (DMCH), Sir Salimullah Medical College Hospital (SSMC), Bangabandhu Sheikh Mujib Medical University (BSMMU) and National Institute of Cancer Research & Hospital (NICRH) from July 2013 to December 2014.Total 96 cases were included in this study. Data were collected by detail history, clinical examination, relevant investigation and result were processed manually and analyzed with the help of SPSS. Results: In this study 72 (75%) patients presented with clinically palpable neck nodes and 24 (25%) presented without neck node. Among 24 cases 7 cases was radiologically positive neck node. Out of 96 cases stage III was the highest (50.96%) followed by stage IV (27.01%), stage II (13.52%) and stage I (8.32%). That is 23 (23.92%) patients present with early stage and 73 (76.18%) patients present in late or advanced stage. Level l was the highest 49 (61.71%), followed by level all 35(44.1%), level lll 10 (12.6%). Conclusion: As cervical lymph node metastasis is a critical event for patients with squamous cell carcinoma of oral cavity, as this is the most reliable predictor of poor treatment outcomes. Thus for appropriate treatment it is very important to know this pattern of metastases. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 102-108